Urban regeneration process as an asset to rise active citizenship: the human cities experience with using photostories as a trigger - Niksic, Matej; Tominc, Biba; Gorsic, Nina (AESOP, 2017)
While the rapidly developing world is facing a rapid urban growth, these processes have been in a full swing much earlier in the s. c. western world. Many of the western cities thus face a need for a redevelopment and regeneration of the already aged-up urban quarters constructed in the periods of their fast growth. Typical examples are the modernist urban neighbourhoods built in the decades after WWII which offered new standards of living when constructed, but need renewal and up-gradings to cope with the needs and expectations of contemporary urban population that is much more individualised in its lifestyles. The paper puts light on the new approach to participatory urban regeneration process that is developed around reveal ingresidents' perceptions of their living environments through crowdsourced analytical photography and attached descriptions. The approach was developed in Ljubljana, Slovenia, as an experimentation programme of the European Human Cities project running from 2014-2018 in eleven European countries. The project aims to encourage and enable civil society across Europe to actively contribute to urban regeneration of living environments in participatory way.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017